PERSEPSI MASYARAKAT TENTANG PERKAWINAN SASUKU DI NAGARI AIR DINGIN KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Yurnelis, Yurnelis; Arifin, Zainal; Anggreta, Dian Kurnia (Pendidikan Sosiologi, 2013)
This  thesis  explain  about  society  opinion  of  those  doing  the  Marriage  Sasuku  in Nagari Air Dingin at Lembah Gumanti district at Solok regency who see couples daily life that  having  marriage  sasuku  and  society  perception  of  the  couples  that  doing  marriage sasuku.  This  study  aimed  to  describe  society views  about  marriage  sasuku  in  Nagari  Air Dingin  at  Lembah  Gumanti  district  at  Solok  regency  and  describe  the  sanctions  if  the marriage sasuku had happened at Nagari Air Dingin society at Lembah Gumanti district at Solok regency. In doing this research, the writer use a fenomenologi theory that according to Alfred  Schurt.  This  research  use  qualitative  research  approach  using  descriptive  research type. Informants in this research is using purposive sampling technique that on purpose where is selected samples based on certain characteristics that needed in this research . Data were collected  through  observations  and  interviews.  Data analysis  was  carried  out  interactively.Based  on  the results of  this  research  that  can  be  concluded  that  the  society  perception  of marriage sasuku in nagari air dingin that society has to consider that the couples who do that marriage sasuku is considered as a person who does not have the traditional, crazy people, there  are  same  with  animals,  and  those  that  are  not  expected  polite.  Also  resulted  in  his family life on the verge of contention, and also they have deformed in their generation that cause of the same genetics. Sanctions or fines for people who are given to couples who have marriage sasuku in Nagari air dingin as expelled from their village, ostracized from society, and even in wearing fine with paying as to kill one head of cattle ( cow, goat, buffalo ) and invite the whole peope of village for a bite to eat. It has been a tradition since formerly in Nagari Air Dingin.